2014
DOI: 10.1097/nnr.0000000000000020
|View full text |Cite
|
Sign up to set email alerts
|

Fear of Hypoglycemia in Women and Men With Type 1 Diabetes

Abstract: In this sample of Norwegian adults with type 1 diabetes, women expressed more concerns about hypoglycemia than men. The highest HFS-II-Worry scores occurred in the same items in women and men, but the largest gender differences in mean scores appeared across a variety of other items, some of which were related to social esteem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 1 publication
3
23
2
2
Order By: Relevance
“…In adults, Barone et al (2015) reported that longer sleep latency was associated with greater GV and those with the greatest GV had significantly more disruptions in sleep. Both longer sleep FOH continues to be a major concern at night ( Gjerlow et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In adults, Barone et al (2015) reported that longer sleep latency was associated with greater GV and those with the greatest GV had significantly more disruptions in sleep. Both longer sleep FOH continues to be a major concern at night ( Gjerlow et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Psychological states are also closely linked with sleep (Akerstedt, Kecklund, & Axelsson, 2007). Fear of hypoglycaemia (FOH) places a major psychological burden on individuals with T1DM (Gjerlow, Bjorgaas, Nielsen, Olsen, & Asvold, 2014), which can affect sleep quality.…”
Section: Introductionmentioning
confidence: 99%
“…In a cross-sectional survey performed in 2011, questionnaires were posted to all adults with Type 1 diabetes (n=636) who attended the diabetes outpatient clinic at St. Olavs Hospital in Trondheim, Norway. The inclusion criteria, prevalence of IAH, and hypoglycaemia symptom profiles in this cohort (13), and the differences in aspects of FoH between women and men (19), have been published previously. The questionnaires used in the survey were forward-backward translated (20) into Norwegian by professional translators, as recommended.…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…The questionnaires used in the survey were forward-backward translated (20) into Norwegian by professional translators, as recommended. The frequency of SH (with loss of consciousness, seizures, or the need for assistance) and self-measurement of blood glucose was queried (13,19). Information on diabetes duration and the most recent HbA1c was obtained from medical records.…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…12 In a survey of 764 Swedes with T1D, both symptoms of being worried and fear in situations of being alone were associated with frequency of severe hypoglycemia and with the number of symptoms during mild hypoglycemia. 13 Again, FoH was greater among women than men.…”
mentioning
confidence: 99%